The Influence of Shopee Advertising, Online Customer Reviews, and Online Customer Ratings on Purchase Interest on the Shopee Marketplace - Dwi Saputri, Cindy Chareynina; Hariasih, Misti; Sari, Dewi Komala (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
Technological advances have resulted in changes in consumer behavior, from offline shopping to online shopping. This study aims to determine the effect of Shopee advertising, online customer reviews, and online customer ratings on purchase interest in the Shopee marketplace. This study uses a quantitative method with the population being Shopee marketplace users in the Sidoarjo area. The sampling technique for this study uses non-probability sampling with a purposive sampling method and the number of respondents is 100 people. The data collection technique is carried out by distributing questionnaires measured on a Likert scale. The data analysis technique for this study uses multiple linear analysis with the help of the Statistical Package for the Social Sciences version 22.0 for Windows program. The results of this study prove that Shopee advertising, online customer reviews, and online customer ratings have an effect on purchase interest, while the effect is positive and significant.